PENGEMBANGAN MATERI INTERAKSI TEMAN SEBAYA SISWA SMA - Putra, Robby Satria; Umari, Tri; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims at developing materials peer interaction tenth grade high school students / MA or equivalent, and a description of its feasibility in terms of aspects of clarity, systematics, image support, freshness, completeness of the materials, and support for video or games. This type of research is the development of research with data analysis techniques using data validity. Sources of data obtained from the lecturers I, supervisor 2, four people BK teachers and 30 students of class X Mia SMA 1 Pekanbaru. The results showed that the material has been developed peer interaction with the overall quality of the material aspects Very Good. So that the material is fit for use by teachers in school guidance and counseling.Keywords: interaction, peers.